2015
DOI: 10.1007/s11244-015-0424-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Cu-Modified Ni/SiO2–Al2O3 Catalysts for the Conversion of Maleic Anhydride to γ-Butyrolactone in Gas Phase

Abstract: The gas phase hydrogenation of maleic anhydride (MA) to succinic anhydride (SA) and the subsequent hydrogenolysis to c-butyrolactone (GBL) was studied on SiO 2 -Al 2 O 3 -supported Ni catalysts modified with Cu and prepared by incipient wetness impregnation (Ni-I, CuNi-I) and coprecipitation-deposition (CuNi-PD) methods. The samples were characterized by N 2 adsorption at -196°C, X-ray diffraction, temperature-programmed reduction, transmission electron microscopy and H 2 chemisorption. Catalytic tests were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This compared with a nearly 90% SA yield at 120 °C in the present work. Previous work suggested that small Ni 0 particle sizes were responsible for high catalytic activity, which may explain the present results for the spinel-derived catalysts with highly dispersed, small Ni 0 species [21].…”
Section: Effect Of Reduction Temperature On Catalytic Activitysupporting
confidence: 76%
See 1 more Smart Citation
“…This compared with a nearly 90% SA yield at 120 °C in the present work. Previous work suggested that small Ni 0 particle sizes were responsible for high catalytic activity, which may explain the present results for the spinel-derived catalysts with highly dispersed, small Ni 0 species [21].…”
Section: Effect Of Reduction Temperature On Catalytic Activitysupporting
confidence: 76%
“…The main disadvantages of the supported Ni catalysts include high Ni-loading, and deactivation of the catalyst at high reaction temperatures [10,[13][14][15][16][17][18][19][20]. Moreover, Bertone et al [21] investigated the Cu-modified Ni/SiO2-Al2O3 catalysts and found that the Ni 0 active species exhibited high catalytic activity, but they observed deactivation during 3 h of testing. Therefore, it is highly desirable to develop novel Ni-based catalytic systems with enhanced activity and stability for the hydrogenation of MA at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…10 In particular, paraffin oxidation is the original method to produce succinic acid; a calcium or manganese catalyst is employed, and the paraffin is completely converted to a mixture of dicarboxylic acid. 11 Subsequently, distillation, crystallization, and drying are applied to purify the succinic acid. Although this process is well established, the yield and purity of succinic acid are relatively low.…”
mentioning
confidence: 99%
“…Succinic acid is considered to be one of the most important platform chemicals for high value-added derivatives production, , which has been widely used in chemicals, degradable plastics, medicine, food, and other fields. , Nowadays, succinic acid is mainly produced by chemical methods, such as paraffin oxidation, catalytic hydrogenation, and electrolytic reduction. Although these chemical methods have been developed to be a relatively mature tool in industry, these chemical methods usually consume nonrenewable resources and cause severe environmental pollution . Instead, microbial fermentation techniques show many merits, such as renewable substrate for production and mild and green reaction conditions. , Thus, the potential fermentation technique has attracted much more attention for succinic acid production .…”
Section: Introductionmentioning
confidence: 99%